ECONOMIC EVALUATION FOR HEALTH ADVOCACY AND INFORMED POLICY - Maznah Dahlui; Thinni Nurul Rochmah; Ernawaty Ernawaty; Djazuly Chalidyanto (Universitas Airlangga, 2021)
Background: Healthcare resources are limited therefore, adequate, appropriate and timely allocation of resources are important. Decision to invest on health care program can be made from the analysis of the information obtained on the cost and consequences of the various alternative health programs, often known as economic evaluation of health interventions.Aims: This write-up emphasizes on the importance of evidence driven policy of health intervention whereby economic evaluation should be performed to indicate whether investment on health intervention would benefit the country.Methods: Literature review on economic evaluation studies conducted by the first author during her 14 years tenure as academician had been performed. Various studies which applied the cost-effectiveness analysis tools to economically evaluate health interventions and programs in Malaysia and other countries are shared.Results: The economic evaluation studies cut across different programs such as disease prevention and treatment, public health monitoring and control, and implications of health issues to the healthcare system. Many of the findings have been used for advocacy to shape the delivery of more effective health intervention programs in the country.Conclusion: The country will benefit from economic evaluation studies which could provide evidence to assist in policy making on health programs for the country.Keywords: economic evaluation, health programs, policy making